(untitled) (Bangladesh Journal of Plant Taxonomy, 2023)
AmelanchierMedik. belonging to the family Rosaceae includes about 30 species with a high content of biologically active substances. The aim of the study was to determine the morpho-anatomical features of leaves at the adaptation and ontogenesis stages of Saskatoon berry variety ‘Krasnoyarskaya’ (A. alnifolia) and variety ‘Prince William’ (A. canadensis). Saskatoon berry leaves are characterized by hypostomatic and anomocytic, less often anisocytic stomata at all stages of ontogenesis. The study revealed in the average length of the polar axis and the stomata equatorial diameter, depending on the cultivation conditions and genotype. A. canadensis had a larger average stomatal area, a thicker epidermis, a greater height of the palisade chlorenchyma cells, and a higher coefficient of palisade, which made it more resistant to changes in atmospheric precipitation, at all stages of ontogenesis, in comparison A. alnifolia. Bangladesh J. Plant Taxon. 30(2): 185-193, 2023 (December)